Non-magnetic ion site disorder effects on the quantum magnetism of a spin-1/2 equilateral triangular lattice antiferromagnet. (18th May 2022) - Huang, Q; Rawl, R; Xie, W W; Chou, E S; Zapf, V S; Ding, X X; Mauws, C; Wiebe, C R; Feng, E X; Cao, H B; Tian, W; Ma, J; et al.
Abstract: With the motivation to study how non-magnetic ion site disorder affects the quantum magnetism of Ba3 CoSb2 O9, a spin-1/2 equilateral triangular lattice antiferromagnet, we performed DC and AC susceptibility, specific heat, elastic and inelastic neutron scattering measurements on single crystalline samples of Ba2.87 Sr0.13 CoSb2 O9 with Sr doping on non-magnetic Ba 2+ ion sites. The results show that Ba2.87 Sr0.13 CoSb2 O9 exhibits (i) a two-step magnetic transition at 2.7 K and 3.3 K, respectively; (ii) a possible canted 120 degree spin structure at zero field with reduced ordered moment as 1.24 μ B /Co; (iii) a series of spin state transitions for both H ∥ ab -plane and H ∥ c -axis. For H ∥ ab -plane, the magnetization plateau feature related to the up–up–down phase is significantly suppressed; (iv) an inelastic neutron scattering spectrum with only one gapped mode at zero field, which splits to one gapless and one gapped mode at 9 T. All these features are distinctly different from those observed for the parent compound Ba3 CoSb2 O9, which demonstrates that the non-magnetic ion site disorder (the Sr doping) plays a complex role on the magnetic properties beyond the conventionally expected randomization of the exchange interactions. We propose the additional effects including the enhancement of quantum spin fluctuations and introduction of a possible spatial anisotropy through the local structural distortions.